The challenges of managing breast cancer in the developing world- a perspective from sub- Saharan Africa - Edge, J; Buccimazza, I; Cubasch, H; et al. (My University, 2014)
Communicable diseases are the major cause of mortality in lower-income countries. Consequently, local and international resources are channelled mainly into addressing the impact of these conditions. HIV, however, is being successfully treated, people are living longer, and disease patterns are changing. As populations age, the incidence of cancer inevitably increases. The World Health Organization has predicted a dramatic increase in global cancer cases during the next 15 years, the majority of which will occur in low- and middle-income countries. Cancer treatment is expensive and complex and in the developing world 5% of global cancer funds are spent on 70% of cancer cases. This paper reviews the challenges of managing breast cancer in the developing world, using sub-Saharan Africa as a model.
PK
Keywords: Breast Neoplasms; Breast Neoplasms/therapy*; Africa South of the Sahara